Harmoni Tauhid Dalam Wadah Islamic Parenting Pada Kasus Kabupaten Karo Sumatera Utara - Lestari, Inda; Matondang, Husnel Anwar (Kamaya: Jurnal Ilmu Agama, 2024)
The background of this research is the practice of Christianisation that tries to influence the dominant Islamic religious beliefs in the region, to cases of early marriage, free sex, drug abuse, and other juvenile delinquency, these problems cause great concern in an effort to maintain the integrity of religious and moral values. This research aims to explore and examine the concept of tawhid harmony in the context of implementing Islamic parenting in the Siosar relocation area, Simacem Village, Tigapanah District, Karo Regency. The research approach is qualitative method and case study. The data collection method is through interviews with parents and direct observation of parenting practices. The results showed that harmony of tawhid plays an important role in the Islamic parenting approach in the area, with the application of tawhid values that include strong religious understanding, open communication based on Islamic values, strict supervision of children's socialisation, and in-depth understanding of religious concepts. Thus, the findings of this research provide a valuable understanding of how the harmony of tawhid can be a strong foundation in guiding children towards a life in accordance with Islamic teachings, especially in relocation areas such as Siosar, Simacem Village. The concept of harmony of Tawhid in Islamic Parenting is not only relevant, but also a solid foundation in guiding children in the context of relocation areas such as Siosar, Simacem Village.